HAMBATAN DALAM PENGELOLAAN WAKAF PRODUKTIF - Purwanto Purwanto (STAI Syubbanul Wathon Magelang, 2017)
One alternative that is expected to overcome the problem of poverty is the active participation of the community in developing cash waqf or management of productive waqf. If the potential of this waqf can be coordinated and managed properly, then this can provide an alternative contribution to the positive solution to the problem of poverty. However, the potential of waqf cannot be utilized optimally because of obstacles. This study is qualitative research that uses descriptive exploratory research designs. The data collection techniques used are conducting interviews and documentation. The data analysis technique used in this study is descriptive qualitative analysis. The use of the analytical method is in accordance with the type of data produced, namely qualitative data in the form of interviews and documentation, regarding what are the obstacles in the management of productive waqf. After the research was carried out, the results found that the obstacles in the management of the first productive endowments were HR or Nazhir factors. Employment as Nazhir was a side job, so work as Nazhir was carried out if there was free time. Both the allotment property or waqf pledges. In general, wakif, when carrying out waqf pledges, immediately mentions the allocation of waqf assets. Third, the socialization has not been maximized. Fourth is financial or fund factors because managing waqf assets requires no small amount of funds.